Simulation of mobile hybrid power generator system development and energy consumption monitoring applications - Charishun, Mohamad Rofiq; Yusof, Anizam Mohamed; Ab. Rahman, Azmanirah (Penerbit UTHM, 2021)
The use of hybrid systems of multiple sources of electricity consists of two or more combinations of renewable energy sources used to enhance system efficiency and energy balance in the supply. Many people experience problems with power outages due to natural disasters. Don't forget those in the grid who need electricity, give the idea of developing mobile power generator hybrid systems and energy consumption monitoring applications. The objectives of the study were to design, install hardware and software as well as test the feasibility of mobile power generator hybrid systems and energy consumption monitoring applications. This product is developed based on the Engineering Design Process (EDP) model which consists of five phases namely analysis phase, design phase, development and implementation phase, testing phase and evaluation phase. The products of this system will be successfully developed by generating electricity and providing power readings to consumers through the Blynk application through internet access. Finally, with the development of this product will reduce the problem of getting an emergency supply. In addition, the features of a portable system provide energy everywhere and can be stored in small areas.